Length, but Not Reactive Edges, of Cup-stack MWCNT Is Responsible for Toxicity and Acute Lung Inflammation. (January 2018) - Hamilton, Raymond F.; Tsuruoka, Shuji; Wu, Nianqiang; Wolfarth, Michael; Porter, Dale W; Bunderson-Schelvan, Melisa; Holian, Andrij
Multiwalled carbon nanotube (MWCNT) toxicity after inhalation has been associated with size, aspect ratio, rigidity, surface modification, and reactive oxygen species production. In this study, we investigated a series of cup-stacked MWCNT prepared as variants of the Creos 24PS. Mechanical chopping produced a short version (AR10) and graphitization to remove active reaction sites by extreme heat (2, 800°C; Creos 24HT) to test the contribution of length and alteration of potential reaction sites to toxicity. The 3 MWCNT variants were tested in vitro in a human macrophage–like cell model and with C57BL/6 alveolar macrophages for dose-dependent toxicity and NLRP3 inflammasome activation. The 24PS and 24HT variants showed significant dose-dependent toxicity and inflammasome activation. In contrast, the AR10 variant showed no toxicity or bioactivity at any concentration tested. The in vivo results reflected those observed in vitro, with the 24PS and 24HT variants resulting in acute inflammation, including elevated polymorphonuclear counts, Interleukin (IL)-18, cathepsin B, and lactate dehydrogenase in isolated lung lavage fluid from mice exposed to 40 µg MWCNT. Taken together, these data indicate that length, but not the absence of proposed reaction sites, on the MWCNT influences particle bioactivity.